Pengaruh Tunjangan Kinerja Terhadap Kinerja Aparatur Sipil Negara (ASN) Pada Kantor Pertanahan Kota Kendari - Fani, Fani; Mustafa, La Ode; Qomariyah, Erni (REZ PUBLICA, 2021)
The purpose of this study was to determine the effect of performance allowances on the performance of state civil servants at the Kendari City Land Office. The Population and sampel in this study at the Kendari City Land Office as many as 33 people. Data collection in this study using a questionnaire and documentation study. The data analysis method in this study is simple linear regression using the SPSS version 23 program. The results of this study indicate that there is a significant influence between the performance of the State Civil Apparatus at the Kendari City Land Office. This is indicated by the coefficient of determination of 26,4% and the remaining 73,6% due to other factors. Then from the research results using simple linear regression analysis shows that the performance allowance X affects the performance of the State Civil Apparatus Y at the Kendari City and Office as evidences by the regression coefficient value which is significant positive Y = 17,376 + 0,465 X (Y = a + b X). The b efficiency is called the regression direction coefficient and states the change in the mean of variable Y for changes in variable X for the increasein the value of b which is positive and decreasesb if b is negative. So that from this equation it can be interpreted: 1.) constans (a) of 17,376 explains that if the independent variable in this case the performance allowance variable is zero (no value), then the performance value of the State Civil Apparatus is 17,376 or is in the category of influence. 2.) OfÂ  0,465% means that if there is an addition, in this case the performance allowance increases by 1 (one) value, it will result in an increases in the performance value StateCivil Apparatus to increases by 0.465. The coefficient is positive, meaning that the performance allowance has a significant effect on the performance of the State Civil Apparatus.